Oxidovanadium(V) dithiocarbamates as driers for alkyd binders - Charamzová, Iva; Vinklárek, Jaromír; Kalenda, Petr; Císařova, Ivana; Honzíček, Jan (Springer, 2020)
A series of oxidovanadium(V) dithiocarbamates were synthesized by the conventional synthetic procedure and characterized by analytical methods. Structures of two representatives were determined by X-ray diffraction analysis on single crystals. The initial screening of catalytic alkyd drying, performed on a commercial solventborne alkyd resin of medium oil length, revealed a promising activity of oxidovanadium(V) dithiocarbamates, which was further proved on several alkyd formulations including slow-drying high-solid binders. Kinetic behavior of the catalyzed autoxidation process, investigated by time-resolved infrared spectroscopy on a thin alkyd film, was found to be very different from commercial cobalt carboxylates. Appearance of oxidovanadium(IV) species upon the curing process was evidenced by EPR spectroscopy. Graphic abstract Oxidovanadium(V) dithiocarbamates were established as primary driers for solventborne and high-solid alkyd formulations. The kinetic behavior of the catalyzed autoxidation process, investigated by time-resolved infrared spectroscopy on a thin alkyd film, was found to be different from commercial cobalt carboxylates. Appearance of oxidovanadium(IV) species upon the curing process was evidenced by EPR spectroscopy.
Dithiokarbamáty oxidovanadičné jako sikativy pro alkydová pojiva
Keywords: alkyd; vanadium; autoxidation; air-drying paints; primary drier; alkyd; vanad; autooxidace; primární sikativ